2004
DOI: 10.1128/jvi.78.24.14053-14056.2004
|View full text |Cite
|
Sign up to set email alerts
|

Association of DC-SIGN Promoter Polymorphism with Increased Risk for Parenteral, but Not Mucosal, Acquisition of Human Immunodeficiency Virus Type 1 Infection

Abstract: There is considerable debate about the fundamental mechanisms that underlie and restrict acquisition of human immunodeficiency virus type 1 (HIV-1) infection. In light of recent studies demonstrating the ability of C type lectins to facilitate infection with HIV-1, we explored the potential relationship between polymorphisms in the DC-SIGN promoter and risk for acquisition of HIV-1 according to route of infection. Using samples obtained from 1,611 European-American participants at risk for parenteral (n ‫؍‬ 71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 17 publications
1
87
2
Order By: Relevance
“…The participation of DC-SIGN in HIV infection has prompted studies to identify either DC-SIGN variants or polymorphisms that correlate with reduced or increased risk of HIV-1 infection. Heterozygosity of a DC-SIGN variant affecting the "neck" domain has been proposed to reduce the risk of HIV-1 infection (46), whereas a large study on the European-American population at risk for HIV infection has revealed that a single-nucleotide polymorphism in the DC-SIGN promoter associates with an increased risk for parenteral HIV-1 infection (19). This polymorphism affects a nucleotide included within the Ϫ468/Ϫ19 region and is located upstream of the PU.1-binding sites identified in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The participation of DC-SIGN in HIV infection has prompted studies to identify either DC-SIGN variants or polymorphisms that correlate with reduced or increased risk of HIV-1 infection. Heterozygosity of a DC-SIGN variant affecting the "neck" domain has been proposed to reduce the risk of HIV-1 infection (46), whereas a large study on the European-American population at risk for HIV infection has revealed that a single-nucleotide polymorphism in the DC-SIGN promoter associates with an increased risk for parenteral HIV-1 infection (19). This polymorphism affects a nucleotide included within the Ϫ468/Ϫ19 region and is located upstream of the PU.1-binding sites identified in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of HIV, DC-SIGN mediates virus binding and uptake by dendritic cells, where DC-SIGN-associated HIV remains infectious for prolonged periods of time and efficiently transfers HIV to CD4(ϩ) T cells in lymph nodes, where viral replication occurs (18). The critical function of DC-SIGN in HIV entry and spread is illustrated by the existence of DC-SIGN promoter polymorphisms associated with increased risk of parenteral infection by HIV-1 (19). Therefore, the identification of the regulatory sequences driving DC-SIGN basal and regulated expression might provide valuable information of potential diagnostic and therapeutic relevance.…”
mentioning
confidence: 99%
“…Results, in particular from the analysis of susceptibility to human immunodeficiency virus-1 or M. tuberculosis infection, remain under discussion. 11,[17][18][19][20][21][22][23] The usurpation of DC-SIGN and other family members by pathogens such as retroviruses, Ebola and Mycobacteria might have led to a pattern of distinctive patches or domains with the characteristic of positive selective pressure as a result of a genetic conflict. 6,13 Against this expectation, the evolutionary analysis of the family suggests both a pattern of apparent redundancy of CD209 genes (gene absence and gene loss) and of positive selection in specific lineages, in the context of a general pattern of gene conservation.…”
Section: 35mentioning
confidence: 99%
“…In this context, a recent study indicates that activation of DC by HPV L1-VLP is MyD88 dependent [34]. Polymorphisms in the DC-SIGN promoter were recently reported [35], but their effect on DC-SIGN binding and signaling has not yet been examined.…”
Section: Blocking the Interaction Of L1-vlp With Dc-sign Inhibits Vlpmentioning
confidence: 99%